Identifikasi Fitosterol dengan Kromatografi Gas –Spektrometer Massa pada Ekstrak Kloroform Biji Buah Atung (Parinarium GlaberimumHassk) Asal Kabupaten Seram Bagian Barat, Maluku - Candra Yulius Tahya; Elen Tiwery; Mega Gracelia Monaten; Tryani K. Junita Lumbantoruan (State University of Malang or Universitas Negeri Malang (UM), 2020)
Five main compounds have been identified in the chloroform extract of Atung fruit seeds (Parinarium glaberimum Hassk) which are linoleic acid (8.88%); stearic acid (8.23%); stigmasta-5,22-dien-3-ol,(3β,22E) or stigmasterol (10.37%); stigmast-5-en-3-ol,(3β) or β-sitosterol (19.59%); and stigmast-5-en-3-ol, (3β, 24S) or γ-sitosterol ( 33.74%) through gas chromatography-mass spectroscopy by analyzing the similarity of molecular weight and positive ion mass/charge fragments and based on the comparison of the GC-MS retention time of phytosterols. This study is the first to report the presence of stigmasterol, β-sitosterol and γ-sitosterol in the chloroform extract of Atung fruit seeds (Parinarium glaberimum Hassk). γ -Sitosterol, the epimer of β-sitosterol, has the greatest abundance in the chloroform extract of Atung fruit seeds. Phytosterol compounds namely stigmasterol, β-sitosterol, and γ-sitosterol have been reported to have many benefits such as reducing blood cholesterol levels, antioxidants, anti-diabetic, anti-inflammatory, and anti-cancer.